How Bad Is Labor Market Concentration?: Evidence From Soviet (Urban) Satellites - Nadezhda Zhuravleva (ZBW - Leibniz Information Centre for Economics, 2021)
There is a debate about the labor market concentration being behind the anemic development of US wages over the past decades. The absence of exogenous variations for causal inference complicates this debate. Here, data from other countries can help. I exploit a variation from a quasi-natural experiment rooted in the practice of urban and industrial planning of the Soviet Union. The Soviet planners developed green-field urban satellites and industrial plants hand-in-hand as large lumpy units. This lumpiness creates variations of concentration in Russia's labor markets still today. Using this variation, I find that concentration significantly hurts wages. A 10% increase in the number of firms leads to a 5% increase in wages.
Keywords: E24; J30; J31; J42; 330